The influence between cognitive and motor domains in students from 7 to 9 years (Research, Society and Development, 2020)
Currently, there is a growing increase evidenced by the evaluating bodies about unsatisfactory school performance, or low school proficiency. The development of aspects of memory, learning and the inseparable body-mind relationship for the subject's learning, brings to light the concept of embodied cognition, or embodied cognition, for which the motor system influences cognition, or cognitive development, basically composed of executive functions - set of cognitive skills needed to learn new things, reason or concentrate in the face of a distracting environment - cognitive flexibility, inhibitory control, working memory, problem solving, reasoning and planning. The aim of the present study is to compare motor development and executive functioning in students aged 7 to 9 years, with unsatisfactory (I) and satisfactory (S) school performance. A quantitative cross-sectional study with the following instruments was used as a quantitative methodology: i) TGMD2 (motor test); ii) Trail Test (executive functions); iii) BMI (weight / height ratio); iv) sociodemographic questionnaire; v) evaluation of students' academic performance (according to the school's criteria for concepts of general non-built proficiency - I and under construction - S). The results show that there was no significance in the comparison between motor performance in the school performance groups I and S for this sample; however, significance was found between Executive Functions (Trail Test) and School Performance I and S. It is concluded that both motor development and executive functioning can influence school performance, when these are not properly developed and are below the recommendations in the literature, as evidenced. Studies of this nature are still in small numbers, especially empirical studies in the context of students' school routine; the relevance of the work is also considered through similar international and national researches that demonstrate the concern with the still present dualism body-mind in school. It is hoped that this research can contribute to the emerging interface between the pedagogical and health areas, collaborating so that teaching professionals discuss with greater propriety the concepts of bioecological systems, their affordances, and those related to the new paradigm of embodied cognition, that is, of the corporealized mind, and develop quality opportunities and stimulations for the body / movement of children at school.